1991
DOI: 10.1088/0034-4885/54/9/001
|View full text |Cite
|
Sign up to set email alerts
|

New developments in hard magnetic materials

Abstract: A review is given of the formation, the crystal structure and the magnetic properties of several classes of rare earth based intermetallic compounds that lend themselves as starting materials of permanent magnets. These compounds include R,Fe,.,B, R,Fe& and R,Co,,B and the large class of ternary rare earth compounds having the tetragonal ThMn,, structure. Special emphasis is given to the changes in magnetic properties of R,Fe,, compounds observed after interstitial solution of C or N atoms. The magnetic proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
212
2
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 571 publications
(230 citation statements)
references
References 283 publications
8
212
2
2
Order By: Relevance
“…where k is the Boltzmann's constant and C is the Curie constant and is given by 2 Magnetic moment of an atom or ion in free space is given by where J is the total angular momentum for the electronic system of an atom, which is the sum of the orbital angular momentum L and spin angular momentum S , γ is the…”
Section: Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…where k is the Boltzmann's constant and C is the Curie constant and is given by 2 Magnetic moment of an atom or ion in free space is given by where J is the total angular momentum for the electronic system of an atom, which is the sum of the orbital angular momentum L and spin angular momentum S , γ is the…”
Section: Equationmentioning
confidence: 99%
“…Gilbert referred to this special type of material as hardened iron and this is perhaps the very reason that even today one still speaks of magnetic hardness although there is no direct correlation to the mechanical hardness. 2 Given below, is a timeline chronicling the very notable turning points in the development of magnetism. be packed in and read in ever smaller dimensions has been responsible for the progress along with modern processing technologies which are often shared with Si technology and has been increasing by leaps and bounds for decades.…”
Section: Introductionmentioning
confidence: 99%
“…The facts that all R 2 Fe 17 binary compounds have low Curie temperatures and exhibit easy-plane anisotropy restrict their possible application as permanent magnets. Recently, it was found that the substitution of Ga, Al, or Si could not only facilitate the formation of R 2 Fe 17 carbides with high carbon concentration, but also increase significantly the Curie temperature. Furthermore, the easy magnetization direction ͑EMD͒ of R 2 Fe 17Ϫx M x ͑M ϭGa or Al͒ alloys can be modified by the introduction of M atoms.…”
Section: Introductionmentioning
confidence: 99%
“…These magnets have been built on a century of materials research and optimization beginning with steels and culminating in the development of the most commonly deployed Nd 2 Fe 14 B permanent magnets. 1,2 Along with the Curie temperature T C , the principle figure of merit for a permanent magnet is the energy density |BH max | (measured in the second quadrant of a hysteresis loop), which is effectively controlled by two properties: the remanence and the coercivity. 3 Materials with high remanence-the magnetization remaining in zero external field-have always relied upon the unpaired electrons of the 3d transition metals (e.g., Mn, Fe, Co, Ni), but the coercivity-the material's resistance to demagnetization-derives from different mechanisms: shape anisotropy arising from microstructural morphology; defects and impurities which act as pinning centers for magnetic domain walls; and, at a fundamental level, the magnetocrystalline anisotropy (MCA).…”
Section: Pacs Numbersmentioning
confidence: 99%